Trypanocide usage in the cattle belt of southwestern Uganda - Kasozi, Keneth Iceland; MacLeod, Ewan Thomas; Sones, Keith Robert; Welburn, Susan Christina (Frontiers in Microbiology, 2023)
Systematic infrastructure and regulatory weaknesses over many decades, in communities struggling with animal African trypanosomiasis would be expected to create an environment that would promote drug misuse and risk development of drug resistance. Here we explore rural community practices of livestock keepers, extension officers and drug shop attendants to see whether appropriate practice was being followed in administration of trypanocides and other drugs. A survey was undertaken in SW Uganda in 2022 involving 451 farmers who kept cattle, sheep or goats and 79 'professionals' (livestock extension officers or drug shop attendants). Respondents reported using one or more type of trypanocidal drugs on 80.1% of the 451 farms in the last 30 days. Diminazene aceturate (DA) was used on around three-quarters of farms, while isometamidium chloride (ISM) was used on around one-fifth. Homidium bromide was used on < 1% of farms. On two-thirds of farms, trypanocides were prepared and injected by farmers, with extension officers administering these drugs on most of the other third, especially cattle farms. Almost all drugs were obtained from privately-owned drug shops. For treatment of AAT prescription-only medicines were routinely used by farmers without professional supervision and without a definitive diagnosis. Farmers were more likely than professionals to only use DA to treat trypanosomiasis and more likely to use additionally use antibiotics to treat the animal, they estimated, on average, that twice the recommended dose of trypanocide was needed to treat a hypothetical 400 kg bovine. A minority of farmers and professionals reported observing withdrawal times following injection of trypanocides and very few knew the withdrawal times for milk or meat. Only one in six farmers appeared to use the sanative pair recommended to reduce the risk of drug resistant trypanosome strains emerging, but this was more widely used by professionals. In addition to trypanocides, most farmers also reported using a topical veterinary pesticide to control ticks and tsetse. On average, farmers spent 12.2% of their income from livestock sales on trypanocides. This study highlights the complexity of issues involved in the fight against AAT using drug treatment.